Influence of Mechanical Properties of Filling Paste on Overlying Strata Movement and Surface Settlement - Yu-Fei Liu; Xin-Hua Wu; Tao Zhu; Xian-Jun Wang; Guo-Yu Zhang; Zhi-Gang Wang (Shock and Vibration)
In order to study the relationship between coal seam buried depth and surface subsidence and select appropriate filling materials, taking Donggou coal mine as the engineering geological prototype, through mechanical test and theoretical analysis, this paper studies the distribution characteristics of in-situ stress and the selection of paste filling materials and their proportion test. The influence of different filling strengths on the overburden movement law and surface settlement law of the working face is analyzed. Based on the experimental research and measured research results, the appropriate filling material is selected. The numerical results show that the material ratio scheme 4 can meet the actual needs of surface subsidence in the process of filling mining. At the same time, the surface subsidence value decreases with the increase of coal seam buried depth.